The mediating role of self-management in the relationship between patient activation and rumination thoughts - Bakir, Ercan; Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz (Elsevier, 2026)
Aim: This study was conducted to examine the statistical intermediary role of self-management in the association between patient activation and rumination in patients with epilepsy. Method: The present study utilized a descriptive and correlational cross-sectional design. A total of 202 individuals diagnosed with epilepsy were recruited through snowball sampling. Data were collected via an online survey between January and May 2025. The research instruments included a Personal Information Form, the Patient Activation Measure (PAM), the Epilepsy Self-Management Scale (ESMS), and the Event-Related Rumination Inventory. Results: In the study, the mean total PAM score was 35.04 +/- 9.34, and the mean total ESMS score was 117.87 +/- 21.00. Also, the mean total Intrusive Rumination score was 13.16 +/- 5.73, and the mean total Deliberate Rumination score was 15.65 +/- 5.87. Positive and statistically significant relationships were found between patient activation and epilepsy self-management; negative and statistically significant relationships were found between patient activation and self-management and both intrusive and deliberate rumination (p < 0.001).The model revealed that patient activation accounted for 57% of the variance in self-management, while explaining 43% of intrusive and 44% of deliberate rumination. Mediation analyses confirmed that epilepsy self-management served as a significant statistical intermediary in these associations. Conclusion: The findings indicate that patients with epilepsy exhibit Level 1 activation and moderate self-management, with deliberate rumination being more prevalent than intrusive rumination. Greater patient activation appears to bolster self-management skills, which subsequently mitigates both deliberate and intrusive rumination.
Keywords: Epilepsy; Patient Activation; Rumination; Self-Management; Nurse